Evaluation of dry saccharine as feed supplement for dairy cows during the dry season. - Zamora, Reina; Solano, Romeo (Agronomía Mesoamericana, 2016)
This research was conducted in Region I in Nicaragua to evaluate the use of saccharine (enriched sugar can e) as feed supplement for dairy cattle on a 65 day experimental period during the dry season, using the statistical design of overchange, with four sub-periods of 14 days each. Six (three per group) crossed-bred cows (Brown Swiss x Zebu) were used. They were selected according to their lactating period, age, milk produc-tion and calving date. Before starting the trial, the cows weighed an average of 500 kg and were producing 8 liters of milk per day, in one milking. The experimental group was fed (ad libitum) 4.12 kg of saccharine, after the milking. The results show that the effect of the saccharine on the milk production was highly significant (P>0.01) therefore we con-cluded that the use of saccharine as a feed supplement for this type of cattle is convenient and recommendable.